(untitled) (PERcursos Linguísticos, 2021)
This article aims to analyze the sociocognitive nature of the construction of referents in the texts. To carry out this work, we follow the assumption that the action of referring is constituted as an activity in which reality is reconstructed through the process of interaction, based on the socio-cognitive activities undertaken by the interlocutors. We established as the main question of our study to analyze how the referential expressions and the other linguistic clues that help in the construction of the referential processes show the sociocognitive nature of the referencing phenomenon. In our analysis, we examined the eminently sociocognitive nature of the referencing phenomenon in three texts belonging to the joke genre. We conclude, with the analysis of the texts, that the referential process is essentially socio-cognitive, since the social and cognitive aspects are intertwined, in the understanding of the texts, which demarcates the essentially dynamic character of the process. To carry out this study, we adopted as theoretical assumptions the referential postulates, as, mainly, Mondada and Dubois (2003), Cavalcante (2012), Custódio Filho (2011) and Cavalcante, Custódio Filho and Brito (2014).